The level of serum Tumor Marker CA15-3 in women with Breast Cancer - Huda Hameed Othman; Walaa Najm Abood; Nazar Abdul Hassan Alwakeel (Diyala Journal of Medicine, 2018)
Background: Breast cancer is the most frequently diagnosed type of cancer in women in all world regions. About 1.7 million cases of breast cancer are diagnosed every year. Breast cancer is the most common cause of death in women worldwide. There were approximately 0.5 million deaths worldwide from breast cancer in 2012, several serum tumor markers have been evaluated in breast cancer. CA15-3 is the most important serum biomarkers used for diagnosis and monitoring of breast cancer.